(untitled) (Research, Society and Development, 2022)
Acute Promyelocytic Leukemia (APL) is a type of cancer that mainly attacks blood cells and requires intensive treatments that damage and directly affect health. The treatments used to control APL associated with drugs affect the individual, manifesting side effects. This systematic review aimed to analyze the side effects associated with the treatments used for APL. For this, a systematic review was conducted according to the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). The literature search was carried out in the following databases: PubMed and Web of Science using combinations of the following keywords in English and Portuguese: acute myeloid leukemia, promyelocytic leukemia, M3, treatment, side effects and drugs. Studies that met the following criteria were included in the systematic review: (I) the participants were diagnosed with APL, (II) the patients underwent a treatment protocol for the pathology, (III) the side effects associated with the treatment were described. A total of 31 articles were selected for inclusion in the systematic review. The most frequent side effects associated with the treatment of APL found were: skin reactions, gastrointestinal discomfort, nausea, vomiting and migraine. Based on the results found in this systematic review, it was observed that some side effects frequently appear in patients with APL, regardless of the type of treatment used, namely: nausea, vomiting, skin reactions, migraine and gastrointestinal discomfort.